Analisis Efektivitas Mesin Heidelberg SM72-FP dalam Upaya Meminimalisir Penyebab Downtime pada Perusahaan Offset Printing : (Studi Kasus Pada CV. Multikarya Esanugrah) - Firdah Lestari, Erlina; Mundari, Siti (Fakultas Teknik UMRI, 2024)
This study analyzes the effectiveness of the Heidelberg SM72-FP machine at CV. XYZ to identify and reduce the factors causing downtime that affect productivity. The evaluation was conducted using the Overall Equipment Effectiveness (OEE) method and the Six Big Losses. This analysis also includes the use of Pareto and fishbone diagrams to determine repair priorities and the main causes of time loss. The research results show that the average OEE value before implementation was 73.30%, below the JIPM standard of 85%. The dominant factor causing losses is reduced speed losses (12.63%). After implementing the maintenance strategy by applying the 2 pillars of TPM focused maintenance and autonomous maintenance, the OEE value increased to 75.25%. The proposed strategy includes scheduling preventive maintenance, lubrication, routine checks, and troubleshooting for machine monitoring. With this improvement, the company's productivity showed a significant increase of 1.95%.